A review of the literature on staff training strategies that minimize trainer involvement. (26th July 2020) - Marano, Kathleen E.; Vladescu, Jason C.; Reeve, Kenneth F.; Sidener, Tina M.; Cox, David J.
Abstract: Asynchronous training procedures, which do not require the simultaneous presence of a trainer and trainee, may offer benefits over synchronous training because they may be more efficient, cost‐effective, and easier to disseminate. Additionally, asynchronous training may address low trainer to staff ratios. The purpose of this literature review was to identify studies that used asynchronous training procedures to teach any skill related to job performance. A total of 54 articles (containing 58 experiments) were identified for inclusion. The asynchronous staff training techniques identified included video models, computer‐based instruction, non‐computer based self‐instruction, and self‐instructional packages. The articles were coded according to participant characteristics, settings, training methodology, and outcomes. Results demonstrated that asynchronous training techniques resulted in mastery‐level performance for a variety of skills, although non‐computer‐based self‐instruction had the least consistent outcomes. Future researchers should directly compare asynchronous training strategies, evaluate individual training components, and assess asynchronous training techniques with a wider range of skills.